Penerapan Overhaul Engine Stand Kijang Menggunakan Alat-Alat Spesial Service Tool Di SMK NU 1 Adiwerna Kabupaten Tegal - Amin Nur Akhmadi; M. Taufik Qurohman; Syaefani Arif Romadhon (Madani : Indonesian Journal of Civil Society, 2019)
Vocational High School is the biggest contributor to unemployment in the area, many supporting factors such as the unstable condition of the company. Basically, that is not all, the teaching process for these Vocational Schools is at the forefront of the increase in the unemployment rate of SMK graduates. From the results of community service activities, the following conclusions are obtained: (1) With the community service at Adiwerna District 1 Vocational High School, giving at Adiwerna Nu 1 Vocational School in Tegal Regency, providing knowledge, understanding, and innovation on efficient engine stand overhauls according to operational standards procedure; (2) Speeding up the work when the engine stand overhaul practices in competency subjects overhaul the engine with the SOP tool so as to make students competent in their performance practices.